The Hazelbourne ladies motorcycle and flying club : a novel - Simonson, Helen (The Dial Press, 2024)
"Constance Haverhill is without prospects. Her mother has just passed away, her brother is newly married, and now that the Great War is over, she has been asked to give up managing the estate she helped to run when the men all joined the army. It is suggested to her that she become a governess. But first, she will act as caretaker to Mrs. Fog, an old family friend who is convalescing at a seaside resort. Constance is soon swept up in the social whirl of the Meredith Hotel and its colorful inhabitants, most notably, Poppy Wirrall. Poppy wears trousers, operates a taxi and delivery service to employ local women, and manages a ladies' motorcycle club. She and her friends welcome Constance into their circle, despite the differences in their stations-Poppy is, for all her empowered modernity, the daughter of a land-owning gentleman, while Constance has only weeks before she must find a position and a home. Constance soon learns, however, that not everything is as it seems in this pocket of English high society. As her connection to this new group deepens and she makes a powerful impression on Poppy's recalcitrant but handsome brother-a former fighter pilot who recently lost a leg in battle-old secrets come to light. Soon, the women are forced to confront the fact that the freedoms they gained during the war are likely to be revoked as the country settles into a hard-won peace"--